Prediction and expression of microrna targeting interleukin-17a in chondrocytes and synovial fibroblasts isolated from osteoarthritic knee - Ng Jun, Quan (2023)
Osteoarthritis (OA) is a prevalent degenerative joint disorder associated with pain and disability. Dysregulation of microRNAs (miRNAs) and inflammation processes play significant roles in OA pathogenesis, with interleukin-17A (IL-17A) as the key proinflammatory cytokine implicated in the cartilage degradation and synovial inflammation. Understanding the regulation of IL-17A signalling in chondrocytes and synovial fibroblasts are crucial for unravelling the underlying disease mechanisms. This study aimed to predict and determine the expression level of miRNAs targeting IL-17A in chondrocytes and synovial fibroblasts isolated from osteoarthritic knee joints. Bioinformatics tools, including TargetScan, miRWalk, and miRDB were employed to identify potential miRNAs targeting IL-17A. The miRNA with the highest and the lowest predicted binding affinity were selected. DIANA-mirPATH analysis web server was used to identify potential pathways that could be targeted by the selected miRNAs. The expression levels of these miRNAs were assessed via quantitative polymerase chain reaction (qPCR) in isolated chondrocytes and synovial fibroblasts from OA patients. ΔCT value was calculated in the study. Hsa-mir-1913 exhibited the highest predicted binding affinity to IL-17A mRNA, while hsa-mir-514a- 5p showed lower binding affinity. These miRNAs were used as a comparative measure to validate the accuracy of the results obtained from the bioinformatics tools. Target prediction of the expressed miRNAs identified different inflammation-linked pathways that are consistent with the previous studies. The qPCR analysis demonstrated that hsa-mir-1913 showed consistent high expression in chondrocytes and synovium fibroblasts samples (14.36 ± 0.72; 14.12 ± 0.69). On the other hand, hsa-mir-514a-5p (-4.65 ± 0.45; -5.05 ± 0.60) exhibited lower expression in both samples. It is essential to acknowledge that this study represents a preliminary investigation into miRNAs that potentially regulate IL-17A in chondrocytes and synovial fibroblasts of osteoarthritis patients. Further research is needed to fully understand the specific mechanisms and functional consequences of these miRNAs in the pathogenesis of osteoarthritis. This study successfully predicted and detected the expression of miRNA targeting IL-17A in chondrocytes and synovial fibroblasts isolated from osteoarthritic knee joints. The identification of miRNA targeting IL-17A may highlight the intricate role of miRNAs in modulating the inflammatory and degenerative process associated with OA and open new avenues for future research and development of targeted therapies for OA.